2014
DOI: 10.5005/jp-journals-10024-1513
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Evaluation of Topical Fluoride ph and their Effect on Surface Hardness of Composite Resin-based Restorative Materials

Abstract: Aim: The aim of the study was to correlate the pH and fluoride ion uptake with surface hardness of composite resin based restorative materials after topical fluoride application.Methodology: Forty disks of each of test materials Composite (Filtek Z350XT, 3M ESPE, St Paul, MN, USA), Resin modified glass ionomer (Vitremer) and Compomer (Dyract AP) were made and ten disks of each material were placed in different test solutions -1.23% APF gel, Sodium fluoride mouth rinse, 0.9% neutral fluoride and distilled water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Both fluoride-treated nano-filled and bulk-fill resin composites showed VHNs comparable to those of their controls (aged with no surface treatment), while both flowable and micro-hybrid composites showed lower hardness values than their controls. Many studies [ 45 , 46 , 47 ] reported controversial effects of the acidulated phosphate fluoride (APF) preparations on composites’ surface hardness and some of their authors [ 47 ] related that controversy mainly to the differences in composites’ filler contents (loading, size and type) and to the composite-APF contact times. The APF gel was found to damage the resin matrix, the inorganic fillers and the resin-filler interfaces, leading to separation of the filler particles [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both fluoride-treated nano-filled and bulk-fill resin composites showed VHNs comparable to those of their controls (aged with no surface treatment), while both flowable and micro-hybrid composites showed lower hardness values than their controls. Many studies [ 45 , 46 , 47 ] reported controversial effects of the acidulated phosphate fluoride (APF) preparations on composites’ surface hardness and some of their authors [ 47 ] related that controversy mainly to the differences in composites’ filler contents (loading, size and type) and to the composite-APF contact times. The APF gel was found to damage the resin matrix, the inorganic fillers and the resin-filler interfaces, leading to separation of the filler particles [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The micro-hybrid type, at the same time, seemed more resistant to the erosive effect of the APF gel, as such surfaces showed lower roughness values than the other types of tested resin composites. Since the restorative composite degradation appears to depend on the filler size distribution through the number of matrix–filler interfaces, this finding could be referred to the material’s higher volumetric filler loading with different size distributions that allow minimal resin content to be exposed to the erosive acidic environment ( Table 1 ) [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , ...…”
Section: Discussionmentioning
confidence: 99%
“…Between composite and fluorides, three major interactions can be noticed, that is, with organic matrix (BisGMA), filler matrix coupling agent and with reinforcing fillers. 2 …”
Section: Discussionmentioning
confidence: 99%
“… 1 It is a chronic, multifactorial, transmissible infectious dental disease that has an adverse effect on a great deal of the world's population, causing both pain and discomfort. 2 In the primary dentition, glass ionomer cement and composites are the most commonly used tooth-colored restorative materials. 3 …”
Section: Introductionmentioning
confidence: 99%
“…The pH and the F − of the prophylactic remineralizing agents influence the corrosion of the various dental materials 24,31,32) , but the HF concentration should be used to give more accurate prediction for the release of ions from the NiTi alloys.…”
Section: Discussionmentioning
confidence: 99%